SISTEMA DE VALORACIÓN DE MONUMENTOS ARQUEOLÓGICOS EN PLANES DE MANEJO. EL CASO DEL PLAN MAESTRO DE MANEJO Y CONSERVACIÓN DE KUELAP Y SU ENTORNO - Bolaños, Aldo (2009)
There appears the system of evaluation of archaeological monuments developed for the Main Plan of Handling and Conservation of Kuelap and his environment (PMK) in 2003. The importance of the article resides in the possibility of including new descriptive parameters of archaeological patrimony in function to the need to develop plans of management that guarantee his conservation and that regulate the interventions that in them are realized. There appear the methodological aspects of the used system of evaluation and his principal results in figures and graphs detailed for the discussion about the validity of the method, taking into consideration that there do not exist previous references to the system used in Peru. The article presents the identified places, the arranging of the information and the qualification of the places based on his limitations, potentials and the required activities, the establishment of the Geohistorical Units (UGH), and the development of plan of interventions prioritized by every place and UGH.